Effect of Different Natural Feeds Containing Calcium and Phosphorus on The Growth Rate of Sand Lobster (Panulirus Homarus) In Floating NET Cages - Rita Rostika; Dina Amalia Triyani; Kiki Haetami; Pringgo Dwi Noor Yadi Putra (PT. Publikasiku Academic Solution, 2024)
The purpose of this study is to determine the effect of different natural feeds containing calcium and phosphorus on the growth rate of sand lobster (Panulirus homarus) in floating net cages in Pangandaran Regency. This study used a complete randomized design (RAL) with four treatments and 4 replicates. The treatment given is anchovies (A), shrimp (B), barnacles (C), and golden snails (D) given to sand lobsters for 60 days. The parameters observed in this study included survival, daily growth rate (LPH), feeding efficiency (EPP), specific growth rate based on weight, specific growth rate based on length, and water quality. The results showed that different natural feeds containing calcium and phosphorus showed an increase in all growth parameters. The type of feed that produced the best growth was anchovy feeding with an LPH value of 1.92%, survival of 100%, EPP of 12.65%, specific growth rate based on weight of 116.62 g, specific growth rate based on length of 6.30 cm and water quality range during the study, namely temperature ranging from 27.1 – 29.0 °C, acidity degree (pH) ranging from 7.74 – 8, salinity ranging from 34 – 35 ppt and dissolved oxygen (DO) ranging from 7.05 – 8.70 mg/L.